2021
DOI: 10.3390/jcm10174006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient Factors Affecting In Vitro Characteristics of Subacromial Bursal Connective Tissue Progenitor Cells during Rotator Cuff Repair

Abstract: Unsatisfactory failure rates following rotator cuff (RC) repair have led orthopaedic surgeons to explore biological augmentation of the healing enthesis. The subacromial bursa (SB) contains abundant connective tissue progenitor cells (CTPs) that may aid in this process. The purpose of the study was to investigate the influence of patient demographics and tear characteristics on the number of colony-forming units (CFUs) and nucleated cell count (NCC) of SB-derived CTPs. In this study, we harvested SB tissue ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…These observations expand the understanding of the biologic activity of SBDCs, which is subject to substantial interindividual variability and may be influenced by the vascularity and fatty infiltration of the bursal tissue as well as the size of the rotator cuff tear. 3 , 21 Of note, similar to the findings of the present study, Mg has been shown to promote the proliferation of bone marrow-derived mesenchymal stem cells. 7 …”
Section: Discussionsupporting
confidence: 88%
“…These observations expand the understanding of the biologic activity of SBDCs, which is subject to substantial interindividual variability and may be influenced by the vascularity and fatty infiltration of the bursal tissue as well as the size of the rotator cuff tear. 3 , 21 Of note, similar to the findings of the present study, Mg has been shown to promote the proliferation of bone marrow-derived mesenchymal stem cells. 7 …”
Section: Discussionsupporting
confidence: 88%
“…The isolation method either using enzymatic digestion or mechanical chopping, in all cases, provided sufficient MSC populations [ 59 ], but the age of the donors significantly affected the time to form colonies in culture [ 60 ], which is a typical phenomenon also for tenocytes of the rotator cuff [ 61 , 62 ]. Others reported that it was not patient characteristics but the size of the rotator cuff tear that affects the colony forming unit potential [ 63 ]. Altogether, the stem cell potential seems to be the most striking reason to preserve the subacromial bursa during shoulder surgery, as it can function as a reservoir for healing-promoting cells.…”
Section: Cells Come Into Focusmentioning
confidence: 99%